Induced potential between interacting particles at nanolevels - Gretchikhin, Leonid I.; Latushkina, Svetlana D.; Kamarouskaya, Viktoryia M. (Vojnotehnički glasnik / Military Technical Courier, 2015)
One has substantiated the existence of a potential barrier at the interface of interacting particles. The formation of the potential barrier in the contact area significantly increases the binding energy of the binary interaction. It has been shown which sets of different interactions should be taken into account when establishing the energy of binary binding.
Keywords: binary interaction; potential barrier; binding energy